(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Small and medium enterprises (SMEs) are pivotal to economic development in Nigeria, yet their sustainability is often hampered by poor financial management, particularly inadequate cash flow forecasting skills. This study investigates the impact of cash flow forecasting skills on the development of SMEs in Cross River State, Nigeria, using a cross-sectional survey design. Primary data were collected through structured questionnaires from 400 SME operators in Calabar Metropolis, employing stratified and accidental sampling techniques. Descriptive and inferential statistics, including regression analysis, were used to analyze the data. Findings reveal that proficiency in cash flow forecasting significantly enhances SME performance, with a positive correlation (r = 0.62, p < 0.05) between forecasting skills and business growth metrics such as profitability and liquidity. The study identifies key demographic characteristics of participants, predominantly female (58%) and aged 26–35 (42%), with secondary education as the highest attainment for 53%. Challenges such as limited financial literacy and inadequate training were noted. Recommendations include targeted financial literacy programs and government-supported training to bolster forecasting skills among SME operators. These findings underscore the critical role of cash flow forecasting in fostering sustainable SME growth in developing economies.